Evidence in Civil Law - Croatia - Aras Kramar, Slađana (Law & Society, 2015)
This book portrays evidence and gathering of evidence under the current Croatian regulation relating to evidence and in practice. In this context, the author first analyses the fundamental principles of Croatian civil procedure and law of evidence. Then, the general principles of evidence and gathering of evidence are discussed, as well as the general rule on the burden of proof. The question of gathering of evidence through modern technology (videoconferencing, etc.) in the Croatian law and practice is also discussed. Separate parts of this book contain the analysis of means of proof regulated by the Croatian Civil Procedure Act: inspection of object ('view'), documents, witness testimony, expert testimony, and party testimony. The rules on costs caused by gathering of evidence, including the costs for translation are analysed, as well as the rules on language. The concepts of illegally obtained evidence and illegal evidence in the Croatian law and practice are discussed. This volume contains the report about the Council Regulation (EC) No 1206/2001 and the multilateral and bilateral legal assistance treaties to which Croatia is a party. There are several appendices to this book: a table of authorities according to the Regulation No 1206/2001, and relevant sources of Croatian civil procedure, table of case law on evidence, table portraying a ordinary/common civil procedure timeline, table referring to legal interpretation in the Croatian legal system, and comparative tables focusing on functional differences between national regulation, bilateral legal assistance treaties, multilateral treaties, and Council Regulation (EC) No 1206/2001 on taking of evidence by hearing of witnesses. This book is a result of the Dimensions of Evidence in European Civil Procedure research project commissioned by European Commission, Directorate-General Justice.